Telomere length and regulatory genes diversity as novel well-being biomarkers in broiler chickens (Gallus gallus domesticus Linnaeus) - Badmus, Kazeem Ajasa (2021)
Telomeres are nucleoprotein (TTAGGG repeats) structures that shield the end of chromosomes from degeneration. Telomere length and its regulatory genes have not been well characterized and used for biomarkers of stress in chicken and hence the reason for this study. This study is aimed at focusing on the how telomere length and its regulatory genes could be altered and used as novel well-being biomarkers under the influence of both acute stress (feed restriction and heat stress) and chronic stress (corticosterone administration). The study was conducted at the Institute of Tropical Agriculture and Food Security, University Putra Malaysia. In the experiment 1, fourty (40) birds of equal sizes (1700 ± 100g) were selected from 300 Cobb 500TM broiler chickens and subjected to both feed restriction (60% of the ad-libitum) and heat stresses (34ºC for 6 hours) in group of five (5) replicated 2 times and their controls. Body weight (BW) and body conformation traits (BCT) were significantly (P < 0.05) reduced by feed restriction and heat stress. Both chickens under feed restriction and heat stresses revealed significant (P < 0.05) telomere attrition at week 1. The loss in telomere length was not observable in heat stressed chickens at week 2 but was observed in the feed restricted birds (p < 0.05) at the same week. In the experiment 2, total of one hundred (100) day old Cobb 500TM broiler chickens were used. Five (5) replicates of ten (10) chickens each were fed 30mg/kg diet of corticosterone from two weeks of age for 4 weeks (Cort group) while the rest 50 chickens were made control of the same replicates. Plasma level of corticosterone of Cort fed chickens was evaluated. Feed conversion ratio (FCR) and biweekly body weight were recorded and two chickens from each replicate were sampled from the two groups (corticosterone and control) for organ’s weight determination and histopathology of small intestine, liver, and muscle fibre. In the same experiment, DNA samples were extracted from the whole blood and tissues (muscle, liver, and heart) and used for telomere length determination. RNA samples were extracted from muscle, liver, and heart for the expression profiles of telomere length regulatory genes such as telomeric repeat factor 1(TRF1), chicken telomerase (chTERT), telomere maintenance gene 2 (TELO2), telomeric repeat containing RNA (TERRA) and heat shock transcription factor 1 (HSF1) and mitochondria DNAs such as uncoupling protein 3 (UCP3), cytochrome C oxidase (COX6A1). RNA was also extracted from hypothalamus for the expression profiles of serum amyloid a (SAAL1) and C-reactive protein (CRP). The meat quality traits were measured from the meat sample collected from both groups (Cort fed chickens and control). No significant differences were observed in the plasma Cort level of both groups at week 2 but a substantial difference was reported at week 4. At week 2 and 4 of the stress, body weights of the Cort fed chickens were significantly (P < 0.05) suppressed with increase in feed conversion ratio compared to the control (P < 0.05). The relative weights of liver, small intestine, heart and gizzard were significantly (P < 0.05) higher in the Cort fed chickens compared to their control. Duodenal and the jejunal villi height were both significantly higher in the Cort fed chickens than in the control. The liver morphology of the Cort fed chickens showed sign of apoptosis and unhealthy conditions (liver fibrosis) in both week 2 and 4. Muscle myofibril revealed significantly (P < 0.05) lower diameter in the Cort fed chickens than in the control at both weeks 2 and 4 of the stress. Telomere length revealed significant (P < 0.05) attrition at both week 2and 4 in the whole blood of the Cort chickens. Significant (P < 0.05) telomere length attrition was revealed at week 2 and 4 of the stress duration in all the tissues except in the liver and heart at week 4. It is observed in this study that TRF1, chTERT, TELO2 and HSF1 were significantly (P < 0.05) upregulated in liver and heart of the Cort fed chickens at week 4 but they were all significantly (P < 0.05) upregulated in the liver at week 2. However, they were all significantly (P < 0.05) downregulated in the muscle at both week 2 and 4. TRF1 and TELO2 were upregulated (P < 0.05) in the heart at week 2 while TERRA and HSF1 were downregulated (P < 0.05). Mitochondria DNAs were significantly (P < 0.05) upregulated in all the tissues at week 2. Acute phase protein factors were significantly (P < 0.05) upregulated in the Cort fed chickens. The meat pH of the Cort fed chickens was significantly (P < 0.05) reduced at week 2 whereas at week 4, it was significantly higher compared to the control. Drip loss was significantly higher at both week 2 and 4 in the Cort fed chickens compared to the control. The meat of the Cort fed chickens showed significantly (P < 0.05) higher redness and lowered lightness at week 4. The shear force of the Cort fed chickens was significantly (P < 0.05) higher than that of the control at week 4. The correlation between telomere length of the chickens used in this study revealed that there is strong and positive relationship (r = 0.62, P < 0.05) between telomere length and the pH and the correlation between telomere length and the drip loss was significant and negative (r = -0.59, P < 0.05) at week 4. The results of the meat quality obtained in this study revealed that the Cort fed chickens possess poor meat quality and these could be responsible for the telomere attrition. The regression model indicated that pH could be used to predict the telomere integrity. The present findings demonstrated that telomere length is well characterized and shortened with stresses (acute and chronic). Telomere length was shortened with feed restriction at 60% of the ad-libitum feed, heat stress at 34 ºC temperature for 6 hours per day and corticosterone feeding at 30mg/kg diet. Therefore, telomere length could be used as a novel well-being biomarker in broiler chicken.